Legal Education and Reproductive Education as An Efforts to Prevent Sexual Violence in Celikah Village, South Sumatra - Banjarani, Desia Rakhma; Adnindya, Msy Rulan; Pasyah, Taroman; Nugraha, Muslim (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: The high rate of sexual violence in rural areas demonstrates that this issue is not solely related to the perpetrator's behavior, but also to the community's lack of understanding of victims' legal rights and reproductive health. Therefore, structured, sustainable, and contextualized legal and reproductive education is needed, in keeping with the social and cultural values of rural communities.Purposes of The Devotion: So that village officials can form or create new policies that are needed to prevent and overcome sexual violence in the Celikah Village area.Method of The Devotion: The activity model in the form of legal counseling uses a visitation model, namely a community service activity carried out by the Counseling Team of Lecturers from the Faculty of Law, Sriwijaya University visiting the target audience of the Celikah Village community, Kayu Agung District, Ogan Komering Ilir Regency. The legal counseling team in this activity uses 2 (two) methods, namely: Presentation and question and answer discussion.Results Main Findings of the Devotion: The "Legal Education and Reproductive Health Education as an Effort to Prevent Sexual Violence in Celikah Village, Kayuagung District, Ogan Komering Ilir Regency, South Sumatra" activity demonstrated excellent acceptance. This was evident in the high enthusiasm of the Celikah Village community to attend and participate in the educational activity, as evidenced by the active involvement of participants during the discussion session. Participants were not merely passive listeners, but also provided responses, asked questions, and responded to the presentations given by the speakers, creating a dialogic and interactive atmosphere. Active community involvement in this forum demonstrated that the legal and reproductive health education materials presented were relevant to the social conditions and knowledge needs of the local community.